How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4701259 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4701259 2339240:K42SWARR 2405685:DGECLZII 2405685:J83BVHG6 2405685:UXWEBRCC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
ZenodoArchiveID: 4460344 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4460344 2129771:DDU3QPXM 2339240:5XNMEGSN 2339240:XIRCF4HG 2339240:XXL72KUQ 2405685:2QM825CH 2405685:5RMUBA3Q 2405685:GBS5KW7S
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode